(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The marine Oligocene deposits of Pakistan are exposed in the Baluchistan and Lower Indus Basins. The Baluchistan Basin deposits are referred to the Khojak Formation of Makran Group. They represent three planktic foraminiferal zones, the Globigerina ampliapertura Zone, G. ciperoensis Zone and Globorotalia kugleri Zone, corresponding to Early, Middle and Late Oligocene. The Lower Indus Basin deposits of Sind include the Kirthar and Nari Formations. On the basis of the larger Foraminifera these deposits are divided into Nummulites fichteli Zone (Early Oligocene), N. fichteli/Lepidocyclina (E.) dilatata Zone (Mid. Oligocene), and L. dilatata Zone (Late Oligocene). The Oligocene deposits are absent in the Upper Indus Basin due to the orogenic movement which took place at the end of the Eocene and continued in the Oligocene.